1991
DOI: 10.1093/sleep/14.5.386
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and Use of Hypnotics: Study of a French Population

Abstract: A cross-sectional study of insomnia and hypnotic use was performed in a sample of the French population. The quota method was used to select the sample of 1,003 subjects, with less than 3% substitution. Subjects were 15 years old and older and were representative of the French population based on gender, age, marital status and living environment. Subjects were asked questions relevant to the complaint of insomnia and hypnotic use and filled out questionnaires measuring anxiety and depression. The complaint of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
79
3
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(99 citation statements)
references
References 0 publications
13
79
3
4
Order By: Relevance
“…This observation corroborated with previous studies. [4,5] This implicate that the prevalence of insomnia in urban India is no less than the developed world. In this study, the prevalence of insomnia increases with age and was found statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation corroborated with previous studies. [4,5] This implicate that the prevalence of insomnia in urban India is no less than the developed world. In this study, the prevalence of insomnia increases with age and was found statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Studies around the world among general population showed that the prevalence of insomnia ranges between 10% and 48%. [4][5][6] Much of this variation of prevalence may be explained by the use of different definitions of insomnia in those studies. [3] Insomnia can have important consequences for sufferers and may affect health, work, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies of sleep disorders among working and general populations, such as the surveys of workers in small and medium-size businesses in the Paris area (33), of a general working population (34), and of the general French populatioil (35), have show11 that gender and age affect self-reported sleep disturbances. Jacquinet-Salord et a1 (33) and Butat et a1 (34) studied the eflects of certain factors in the work environment on sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The current use of hypnotics in the general population is estimated to range between 3.5% and 11.7%, doubling in elderly populations [8][9][10][11]. Hypnotics may produce residual daytime sleepiness and impairment of psychomotor, attention and memory performances the day after bedtime administration, especially with the high dose and long half-life durations [12].…”
Section: Introductionmentioning
confidence: 99%